"Warm as a Departed Friend": In Remembrance of Hu Xudong. Issue 1 (2nd January 2022) - Goodman, Eleanor
Abstract : Hu Xudong was born on October 30, 1974, in Chongqing, Sichuan, and died tragically on August 22, 2021, in Beijing. He was a poet, academic, and prolific columnist and essayist who will be greatly missed for his sparkling wit, humane touch, and acute social observations. For many years, he taught at Peking University in the Institute for World Literatures in the School of Foreign Languages, and served as the deputy director of the PKU Brazilian Cultural Center. He produced four formally published books of poetry as well as several self-published collections, in addition to hundreds of newspaper columns and essays. Hu is survived by his wife, Zhou Shu, a reporter and writer, and his young daughter, Daodao.